Designing Bio-Based Color Sensor from Myofibrillar-Protein-Based Edible Film Incorporated with Sappan Wood (Caesalpinia sappan L.) Extract for Smart Food Packaging - Iis Rostini; Junianto; Endang Warsiki (Applied Sciences, 2023)
The use of intelligent sensor-based packaging in food products allows the quick evaluation of food quality. This study aimed to design a color sensor from surimi utilizing sappan wood extract (SWE) for intelligent food packaging. The myofibrillar-protein-based edible film incorporated the SWE at different concentrations (0.15%, 0.25%, and 0.35%). The physical properties of the sappan wood–surimi edible film (SSEF) were analyzed, and the color changes at various pH levels and soaking times under different conditions were assessed. According to the results, different concentrations of the SWE significantly affected the thickness, transparency, tensile strength, and elongation at break of the film. However, the values were still within the acceptable range. The pH values increased the film’s darkness, redness, and blueness. Based on the evaluation of the SSEF under different soaking conditions, the color changes of the film in acidic conditions were more stable than in neutral and alkaline conditions. This study showed that SSEF can be used as intelligent food packaging. It can act as a color sensor due to its sensitivity to the changes in the pH condition of the product.